Pengaruh Pengelolaan Kearsipan terhadap Kinerja Pegawai Dinas Perpustakaan dan Kearsipan Kota Ambon - Dewi Nanulaitta; Jean Rosalina Asthenu (P3M Politeknik Negeri Ambon, 2024)
Records management is important for an organization where good records management will increase the success or performance of an agency's employees. Based on the results of observations made at the Ambon City Library and Archives Service Office, it shows that archive management at the Ambon City Library and Archives Service Office is not optimal. This can be seen from the lack of accuracy of employees in storing records and inadequate facilities. This research aims to determine and analyze the influence of archives management on the performance of Ambon City Library and Archives Service employees. The analytical method used in this research is quantitative analysis and simple linear regression. Archives management at the Ambon City Library and Archives Service has an average value of 3.51 which is interpreted as good, and employee performance has an average value of 3.68 which is interpreted as good. The results of hypothesis testing for Archives Management on Performance obtained a calculated t value of 8.471 so it can be concluded that archives management has a positive effect on performance. The results of the coefficient of determination show that the influence of archives management on employee performance at the Ambon City Library and Archives Service is 71.9% while the remaining 28.1% is influenced by other variables. Based on these results, it can be concluded that the better the records management, the better the employee performance. Efforts to improve archives management by providing archivists with the opportunity to take part in archives training to become more skilled at work. Keywords: Archives Management, Performance